Spatial Effects of European Integration: Do Border Regions Benefit Above Average? - Annekatrin Niebuhr (Hamburg Institute of International Economics (HWWA), 2004)
A basic result of new economic geography (NEG) models is that the proximity to consumer markets impacts wages and employment within regions. The ongoing process of European integration, being targeted on the reduction of barriers to trade and factor mobility, has presumably changed relative market access in Europe. The present paper aims at providing some evidence on spatial effects of integration released by declining border impediments and changing market potentials. The analysis departs from a threeregion economic geography model. We focus on the impact of integration on European border regions and the question whether they realise above average integration benefits. The empirical analysis concerns integration effects in the EU15 regions arising from a reduction of non-tariff and other barriers since the mid 1970s.
Keywords: R12; F15; C21; 330; New economic geography; market access; European integration; border regions; Europäische Integration; Marktintegration; Grenzgebiet; Neue ökonomische Geographie; EU-Staaten